The real estate investment handbook - Haight, G. Timothy (John Wiley & Sons, 2005)
Throughout the book, experts G. Timothy Haight and Daniel D. Singer offer careful examinations of the various types of commercial real estate available, the measures within the markets used to evaluate their performance, and the intricacies of the markets in which they are traded. The discussions of breakeven analysis, present value, financial leverage, loan packaging, and practical real-life situations found in The Real Estate Investment Handbook will help you make better-informed decisions when investing in properties such as: * Apartments, condominiums, and time-shares * Single-family homes * Self-storage facilities * Office buildings * Industrial properties * Parking lots * Shopping centers * Hotels and motels